2008
DOI: 10.1093/ndt/gfn654
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with cinacalcet and conventional therapy reduces parathyroid hyperplasia in severe secondary hyperparathyroidism

Abstract: Background. The effect of cinacalcet on the structural pattern of hyperplastic parathyroid glands was evaluated, using high-resolution colour Doppler (CD) sonography, in haemodialysis patients with severe, inadequately controlled, secondary hyperparathyroidism (sHPT).Methods. Nine patients (6 males, 3 females; mean age ± SD, 55.5 ± 12.6 years) received cinacalcet, with adaptation of existing concomitant therapies. Biochemical parameters and the morphology and vascular pattern of hyperplastic parathyroid glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 33 publications
7
71
2
10
Order By: Relevance
“…After PTX, there is a constant decline in renal function, probably due to haemodynamic effects of PTH on the preglomerular and efferent arterioles [49]. It should be noted, however, that current studies suggest that the graft survival is not decreased by PTX [47,132,135,140]. It seems that the risk and intensity of the decrease of renal function are highly dependent on the severity of HPT (high level of PTH) and probably on the slope of decline, and therefore avoiding/reducing post-PTX hypoparathyroidism and hypocalcaemia could reduce the risk of significant decline of the renal function [129] It is therefore expected that a less aggressive parathyroid resection should lead to a less important decline in PTH and therefore to a decreased risk of decline of renal function.…”
Section: Extent Of Surgery In Persistent Hpt After Renal Transplantationmentioning
confidence: 67%
See 1 more Smart Citation
“…After PTX, there is a constant decline in renal function, probably due to haemodynamic effects of PTH on the preglomerular and efferent arterioles [49]. It should be noted, however, that current studies suggest that the graft survival is not decreased by PTX [47,132,135,140]. It seems that the risk and intensity of the decrease of renal function are highly dependent on the severity of HPT (high level of PTH) and probably on the slope of decline, and therefore avoiding/reducing post-PTX hypoparathyroidism and hypocalcaemia could reduce the risk of significant decline of the renal function [129] It is therefore expected that a less aggressive parathyroid resection should lead to a less important decline in PTH and therefore to a decreased risk of decline of renal function.…”
Section: Extent Of Surgery In Persistent Hpt After Renal Transplantationmentioning
confidence: 67%
“…Its introduction decreases renal function, which is reversible after cessation, suggesting the same haemodynamic effect like PTX. Some studies observed a regression of parathyroid gland volume on ultrasonography with cinacalcet [132,133] (EL 3), but its effect on urinary calcium excretion is not known and studies reported contradictory results (unchanged, increased or reduced calcium excretion) [107]. Above all, cinacalcet is only approved for treatment of renal HPT and is very expensive [134] (EL 2), rendering PTX as primary effective and longterm option for transplanted patients.…”
Section: Early Versus Late Parathyroidectomy In Tertiary (Post-renal mentioning
confidence: 99%
“…More recent studies suggest that combined therapy with cinacalcet and low doses of vitamin D sterols could be an effective strategy to treat SHPT while adequately maintaining acceptable levels of calcium and phosphorus (22)(23)(24). However, there is controversy as to whether cinacalcet is capable of controlling parathyroid hyperfunction in patients with marked parathyroid hyperplasia (25,26). In addition, although experimental studies suggest that regression of parathyroid hyperplasia could be induced by calcimimetics (27,28), this possibility has not been adequately explored in the clinical setting (26,29).…”
mentioning
confidence: 99%
“…However, there is controversy as to whether cinacalcet is capable of controlling parathyroid hyperfunction in patients with marked parathyroid hyperplasia (25,26). In addition, although experimental studies suggest that regression of parathyroid hyperplasia could be induced by calcimimetics (27,28), this possibility has not been adequately explored in the clinical setting (26,29).…”
mentioning
confidence: 99%
“…18,19 Long-term combination of cinacalcet with standard therapy has been shown to reduce parathyroid hyperplasia. 20 …”
Section: Introductionmentioning
confidence: 99%